Understanding obesity - Yao, Wynette (Discovery Channel)
With the mix of ever-available food and labour saving technology, obesity is quickly spreading across the globe. Examine the science of fat with scientists whose experiments show that the body has a set weight that it strives to maintain. Hear personal stories of people fighting obesity and the genetic breakthrough that could lead to the first anti-fat drug.